FORMAL, INFORMAL WORK AND LEGAL ORDINATIONS IN BRAZILIAN RECYCLING (Formação (Online), 2021)
AbstractIn the contemporary world, it becomes more and more important to discuss the work relations that are decurrent of capitalism’s ascension. The present article represents an effort in this sense, dwelling precisely in this theme. Two concepts coined by Marx and Engels are utilized here, which are the ones of formal and informal work, under the optics of work relations inside garbage collection and recycling, precisely inside brazilian reality. These activities consist in a contradictory duty, because even though they possess great social and environmental values, the workers do not receive the same recognizement, for their work is based on collecting other people’s consumer waste. Having that thought, it is essential to consider the reasons that take capitalism to incentivize such marginalized activities. The hypothesis under which this article is built is that capitalism does it to maintain the eminence of a small portion of the society, while the other is overexploited.Keywords: Formal work. Informal work. Legal ordinations. Recyclable materials collectors. Recycling.